Inovasi Model Problem Based Learning (PBL) dalam Meningkatkan Pemahaman Teks Pidato pada Siswa di SMP Negeri 1 Banjarmasin - Norhidayah Norhidayah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to describe the innovative application of the Problem Based Learning (PBL) model in improving the understanding of speech texts in grade VIII students of SMP Negeri 1 Banjarmasin. The study uses a descriptive qualitative approach supported by quantitative data in the form of student learning outcomes. Data sources include lesson planning documents (RPP), the